Analyse des effets économiques de la semaine comprimée et des horaires flexibles sur l’entreprise - Proulx, Pierre-Paul; Lagana, Antonio (L'Actualité économique, 1975)
This theoretical article examines the economic effects of compressed and variable work week upon industry. After a definition of the terms of a review of relevant literature, it presents a model which provides some insight into the reasons why management has often taken the initiative in proposing such changes in working hours. It then develops a testable theoretical and empirical model concerning the effects of changes in the work week upon productivity costs and profits in industry.